Prostate – Specific Antigen (Psa) as a Screening Tool for Benign Prostate Hyperplasia (Bph) and Prostate Cancer (Pca) in Sulaimani Province - Muhammad, Sirwan M.; Waheed, Intissar I. (Science Journal of University of Zakho, 2013)
The current study was applied to evaluate the significance of serum Prostate- Specific Antigen (PSA) as a screening tool for the PCa and the role of percent free - to- total PSA ratio in the discriminating between BPH and PCa. Prostatic biopsies and blood were collected from (62) patients aged between (50-89) years. Eleven healthy men with negative digital rectal examination, (median age, 60.6yr) were enrolled in this study as a control group. The common diseases encountered were BPH (59.7%), BPH with prostatitis (19%), adenocarcinoma (17.7%), and transitional cell carcinoma (3.2%). 54% of BPH cases had tPSA level < 4 ng/ml as well 13.5% of them having tPSA>10, while 15.3% of malignant cases had tPSA level < 4 ng/ml and 84.7% of them having tPSA>10. The statistical analysis showed a significant difference between (BPH and PCa); (PCa and control cases) and  (prostatitis and control) in regard to tPSA. Regarding to % cPSA the entire case of PCa showed levels >60% aligned with only 75%, 27%, 16% in prostatitis, control and BPH groups successively. The mean comparison showed statistically significant differences between the PCa patients and control cases and between prostatitis and control cases, while no significant differences between BPH and control group. Regarding to % FPSA, 53.8 % of PCa cases showed ≤15, along with 16.6 % of prostatitis showed ≤15, while no cases of both BPH and control revealed FPSA ≤15. Comparison of the means showed a statistically large difference between the (PCa and BPH), (PCa and control) and (prostatitis and control) cases. While no significant differences between (BPH and control) cases. In conclusion, combinational use of tPSA with other molecular forms of PSA especially proportion of FPSA provide higher diagnostic and differentiative accuracy than the tPSA alone.
Keywords: Prostatic specific antigen; Free PSA; Prostate cancer; BPH; Prostatits; cPSA; tPSA